34th Aerospace Sciences Meeting and Exhibit 1996
DOI: 10.2514/6.1996-380
|View full text |Cite
|
Sign up to set email alerts
|

Mach 6 testing of a scramjet engine model

Abstract: Testing of a sub-scale scramjet research engine model was carried out in the March 6 Ramjet Testing of a sub-scale scramjet research engine model was carried out in the March 6 Ramjet Engine Test Facility of the National Aerospace Laboratory, Kakuda Research Center. By attaching a Engine Test Facility of the National Aerospace Laboratory, Kakuda Research Center. By attaching a short strut on the top wall, intensive combustion with high combustion efficiency was attained, and short strut on the top wall, intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…2, 14 Further downstream towards the combustor exit, the reactive flow shows a typical wall pressure distribution of supersonic combustion. 15,16 Upstream of the central injector no influence is observed. This shows a good stability of the inlet and the validity of the additional air injection to impose back-pressure.…”
Section: Flight Condition Reacting-casementioning
confidence: 80%
“…2, 14 Further downstream towards the combustor exit, the reactive flow shows a typical wall pressure distribution of supersonic combustion. 15,16 Upstream of the central injector no influence is observed. This shows a good stability of the inlet and the validity of the additional air injection to impose back-pressure.…”
Section: Flight Condition Reacting-casementioning
confidence: 80%
“…[5][6][7][8][9][10][11][12][13][14][15] In the scramjet engine tests carried out in the RJTF it has been found that the difference of engine inner configuration, mainly strut shape, produces large difference of thrust performance in the condition of Mach 6. 5 In addition to the above it has been also found that the fuel cannot spread all over the engine cross section and concentrates to the top wall side.…”
Section: Japan Aerospace Exploration Agency (Jaxa) Has Been Investigamentioning
confidence: 99%
“…Figure 1 shows the outline of the tested engine. [5][6][7][8][9][10][11][12][13][14][15] The engine is rectangular shape having the overall length of 2.1m, width of 200mm and height of 250mm, and consists of inlet, isolator, combustor and nozzle. The whole of side wall is swept back at 45 degrees to deflect the air stream for spillage required in engine starting.…”
Section: ⅱ.A Tested Enginementioning
confidence: 99%
“…The Ref. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] researched the design method and performance of sidewall inlet in detail.…”
Section: Introductionmentioning
confidence: 99%